Integrative Identification of Crucial Genes Associated With Plant Hormone-Mediated Bud Dormancy in Prunus mume - Li, Ping; Zheng, Tangchun; Zhang, Zhiyong; Liu, Weichao; Qiu, Like; Wang, Jia; Cheng, Tangren; Zhang, Qixiang (Frontiers in Genetics, 2021)
Prunus mume is an important ornamental woody plant with winter-flowering property, which is closely related to the bud dormancy. Despite recent scientific headway in deciphering the mechanism of bud dormancy in P. mume, the overall picture of gene co-expression regulating P. mume dormancy is still unclear. Here, a total of 23 modules were screened by weighted gene co-expression network analysis (WGCNA), of which 12 modules were significantly associated with heteroauxin (IAA), abscisic acid (ABA) and gibberellin, including GA1, GA3 and GA4. The yellow module, which was positively correlated with the content of ABA and negatively correlated with the content of GA, was composed of 1,426 genes, among which 156 transcription factors (TFs) were annotated with transcriptional regulation function. Enrichment analysis revealed that these genes related to dormancy process, seed dormancy process and plant hormone signal transduction. Interestingly, the expression trends of PmABF2 and PmABF4 genes, the core members of ABA signal transduction, were positively correlated with P. mume dormancy. Additionally, PmSVP gene has attracted lots of attention because of its co-expression, function enrichment and expression level. PmABF2, PmABF4 and PmSVP were the genes with the high degree in the co-expression network, whose expression was upregulated by ABA treatment. Our results provide insights into the underlying molecular mechanism of plant hormone regulated dormancy and screen the hub genes involved in bud dormancy in P. mume.